Primary Palliative Care for Emergency Medicine (PRIM-ER): Applying form and function to a theory-based complex intervention - Hill, Jacob (Contemp Clin Trials Commun, 2020)
BACKGROUND: Emergency departments are seeing an increase in acute exacerbations of chronic disease in the older-adult population. The delivery of palliative care in the emergency department can increase goal-concordant care at the end-of-life for this population. New interventions in palliative care for emergency medicine require large, pragmatic, complex health interventions due to the heterogeneous and dynamic environment of emergency departments. These complex interventions must balance fidelity with adaptability, while being rooted in theory, to produce an intervention that can be applied in a variety of contexts. METHODS: Primary Palliative Care for Emergency Medicine (PRIM-ER) is a large, pragmatic, complex health intervention. This paper outlines the conceptual theory-based design as well as the study form and functions of PRIM-ER to exemplify how this complex intervention has balanced fidelity with adaptability. RESULTS: A form and function matrix was created to highlight the key objectives and tailored intervention components of PRIM-ER. Each intervention component was also linked to one or more elements of the Theory of Planned Behavior to support provider behavior change and the delivery of palliative care services and referrals. CONCLUSION: The application of theory and delineation of forms and functions, as well prospective adaptation monitoring of large complex interventions can support the balance of fidelity with adaptability to encourage successful interventions among a variety of clinical environments.